Macrolide resistance gene erm(TR) and erm(TR)-carrying genetic elements in Streptococcus agalactiae: characterization of ICESagTR7, a new composite element containing IMESp2907. (17th December 2015) - Mingoia, Marina; Morici, Eleonora; Marini, Emanuela; Brenciani, Andrea; Giovanetti, Eleonora; Varaldo, Pietro E.
Abstract: Objectives: The objective of this study was to investigate macrolide-resistant Streptococcus agalactiae isolates harbouring erm (TR), an erm (A) gene subclass, with emphasis on their erm (TR)-carrying genetic elements. Four erm (TR)-carrying elements have been described to date: three closely related (ICE10750-RD.2, Tn 1806 and ICE Sp 1108) in Streptococcus pyogenes, Streptococcus pneumoniae and S. pyogenes, respectively; and one completely different (IME Sp 2907, embedded in ICE Sp 2906 to form ICE Sp 2905) in S. pyogenes . Methods: Seventeen macrolide-resistant erm (TR)-positive S. agalactiae isolates were phenotypically and genotypically characterized. Their erm (TR)-carrying elements were explored by analysing the distinctive recombination genes of known erm (TR)-carrying integrative and conjugative elements (ICEs) and by PCR mapping. The new genetic context and organization of IME Sp 2907 in S. agalactiae were explored using several experimental procedures and in silico analyses. Results: Five isolates harboured ICE10750-RD.2/Tn 1806, five isolates harboured ICE Sp 1108 and five isolates bore unknown erm (TR)-carrying elements. The remaining two isolates, exhibiting identical serotypes and pulsotypes, harboured IME Sp 2907 in a new genetic environment, which was further investigated in one of the two isolates, SagTR7. IME Sp 2907 was circularizable in S. agalactiae, as described in S. pyogenes . The new IME Sp 2907 junctions were identified based on its site-specific integration; the att sites were almost identical to those in S. pyogenes . In strain SagTR7, erm (TR)-carrying IME Sp 2907 was embedded in an erm (TR)-less internal element related to ICE10750-RD.2/Tn 1806, which, in turn, was embedded in an ICE Sde 3396-like element. The resulting whole ICE, ICE Sag TR7 (∼129 kb), was integrated into the chromosome downstream of the rplL gene, and was excisable in circular form and transferable by conjugation. Conclusions: This is the first study exploring erm (TR)-carrying genetic elements in S. agalactiae .